Deep mutational scanning of the Neisseria meningitidis major pilin reveals the importance of pilus tip‐mediated adhesion - Kennouche, Paul; Charles‐Orszag, Arthur; Nishiguchi, Daiki; Goussard, Sylvie; Imhaus, Anne‐Flore; Dupré, Mathieu; Chamot‐Rooke, Julia; Duménil, Guillaume (The EMBO journal, 2019)
Type IV pili (TFP) are multifunctional micrometer‐long filaments expressed at the surface of many prokaryotes. In Neisseria meningitidis , TFP are crucial for virulence. Indeed, these homopolymers of the major pilin PilE mediate interbacterial aggregation and adhesion to host cells. However, the mechanisms behind these functions remain unclear. Here, we simultaneously determined regions of PilE involved in pilus display, auto‐aggregation, and adhesion by using deep mutational scanning and started mining this extensive functional map. For auto‐aggregation, pili must reach a minimum length to allow pilus–pilus interactions through an electropositive cluster of residues centered around Lys140. For adhesion, results point to a key role for the tip of the pilus. Accordingly, purified pili interacting with host cells initially bind via their tip‐located major pilin and then along their length. Overall, these results identify functional domains of PilE and support a direct role of the major pilin in TFP‐dependent aggregation and adhesion. Synopsis Adhesion mediated by type IV pili enables host invasion in a range of mainly Gram‐negative bacterial pathogens. Deep mutational scanning of the Neisseria meningitidis major pilin PilE uncovers key steps of the type IV pili‐dependent adhesion process. Interaction via the pilus tip initiates bacterial adhesion to the cell surface. During the later phase of host cell adhesion, residues along the length of the pili bind to the cell surface. A threshold pilus length is required to initiate pilus‐pilus interactions leading to bacterial auto‐aggregation and formation of bacterial microcolonies. Graphical Abstract Systematic mutations in pilE uncover two successive modes of type IV pilus‐mediated host cell adhesion and the requirement for a pilus length threshold for bacterial aggregation in the meningococcus.